Scientific Justification of A Personalized Approach To The Management of Patients with Terminal Renal Failure (Bangladesh Journal of Medical Science, 2024)
Currently, there is uncertainty about the ideal treatment for recovery and a personalized approach to the management of patients with terminal renal failure.Therefore, a systematic review was conducted over the past 10 years.Network meta-analysis of randomized control trials (RCTS), which compared the prevalence of chronic renal failure (CRF), according to various literature data. AccordingtoWHOitisfrom 50 to 250 peopleper 1 millionpopulationperyear.Active therapy for terminal CRF (hemodialysis, peritoneal dialysis, kidney transplantation) is received in Western Europe by 500-600 patients, in the USA and Japan - 1000-1200 patients, while in Kazakhstan-about 100 patients per 1 million population per year. The ten-year probability of survival of patients with terminal CRF in active therapy exceeds 50%, excluding patients with diabetes mellitus.Arterial hypertension remains the most frequent symptom, largely determining the prognosis of patients with CRF. Ten-year survival of patients with CRF in combination with hypertension in hemodialysis is lower than in normotensive patients by 30-50%. Successfully performed a kidney transplant can eliminate the symptoms of chronic renal failure.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 851-863